Auricular reconstruction. (28th March 2019) - Cubitt, Jonathan J; Chang, Ling‐Yun; Liang, Derek; Vandervord, John; Marucci, Damian D
Abstract: External ear abnormalities are common. These may affect ear shape, size, prominence and degree of development. They may also be associated with hearing loss. The early identification and management of hearing loss is essential. There are several options for reconstruction of the external ear using both autologous and non‐autologous techniques. The aim of this article is to outline the different reconstructive options.